Relationship Between Pre eclampsia and Underweight Baby in the Obstetrics Unit of Guido Valadares National Hospital in 2023 - da Costa Guterres, Ana Claudia; de Deus, Elisa; Santos Ximenes, Rafael dos; Soares Amaral, Odelia; Jesus Vaz Cabral, Teresa de; Ximenes, António (CV RIFAINSTITUT, 2024)
Pre‑eclampsia is a serious complication that affects the mother's body, childbirth, and postpartum. It is characterized by signs such as hypertension, edema, and proteinuria that occur during the 20 weeks of pregnancy. An underweight baby is a baby who weighs less than 2500 grams. According to data from the Timor‑Leste Demographic Health Survey (TLDHS) in 2016, 215 mothers had pre‑eclampsia and 72 babies died with underweight status. Pre‑eclampsia is one of the complications that kills mothers with a high percentage of 25% and a frequency of 42.According to data from Guido Valadares National Hospital in 2021, 174 mothers had pre‑eclampsia and 58 babies were underweight. To understand the relationship between preeclampsia and underweight baby incidents. This is a descriptive quantitative research with a crosssectional approach. The technique used was Accidental Sampling, with a sample of 64 respondents. The results show that there is a relationship between pre‑eclampsia and underweight baby incidents. 46 mothers (71.9%) had preclampsia and 36 babies (78.3%) were underweight. The relationship between preeclampsia and underweight baby incidents had a p‑value of 0.03. Conclusion: This research shows that there is a relationship between preeclampsia and underweight baby incidents. The information obtained can be used to improve the quality of service provided to mothers with specific focus on pre‑eclampsia and underweight babies.